2020
DOI: 10.1016/j.healthpol.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of physical activity on public health: A review and critique

Abstract: Background While several reviews have assessed economic evaluations of physical activity in public health and, in most cases, found the interventions to be cost-effective, the validity of the conclusions reached depends on the appropriateness of the modelling methods used in the individual studies. Objective To provide an overview and critique of modelling approaches and key structural assumptions used in applied studies to estimate the impact of physical activity on health. Methods Electronic databases were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The evidence-based knowledge of the influence of physical activity (PA) on individual health [ 1 ], as well as an understanding of its influence on public health [ 2 , 3 , 4 ] has grown of late. There is emerging evidence suggesting that participation in physical activity may provide benefits beyond physical health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence-based knowledge of the influence of physical activity (PA) on individual health [ 1 ], as well as an understanding of its influence on public health [ 2 , 3 , 4 ] has grown of late. There is emerging evidence suggesting that participation in physical activity may provide benefits beyond physical health [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first break-even economic analysis of a cycling infrastructure investment and more broadly a physical activity promotion intervention [ 41 ]. An example of such type of assessment can be found within the obesity literature, where Bates et al (2022) estimated the maximum justifiable cost for a weight loss maintenance intervention for individuals at different BMI and type II diabetes risk [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…communities versus city dwelling) 52 . However, this study provides one of the few worked examples on how to conduct a health economic analysis tailored to the decision makers' information needs, which has been often overlooked in economic evaluations [20][21][22] .…”
Section: Limitationsmentioning
confidence: 99%
“…quality-adjusted life years) is greater than the budget spent to implement the intervention. While those studies have found the interventions to be costeffective in most cases 18 , such approaches have been called into question [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%